Gonadoblastoma Y locus genes expressed in germ cells of individuals with dysgenetic gonads and a Y chromosome in their karyotypes include DDX3Y and TSPY. Issue 4 (12th February 2019) - Vogt, P H; Besikoglu, B; Bettendorf, M; Frank-Herrmann, P; Zimmer, J; Bender, U; Knauer-Fischer, S; Choukair, D; Sinn, P; Lau, Y-F C; Heidemann, P H; Strowitzki, T
Abstract: STUDY QUESTION: Which Y genes mapped to the 'Gonadoblastoma Y (GBY)' locus on human Y chromosome are expressed in germ cells of individuals with some Differences of Sexual Development (DSD) and a Y chromosome in their karyotype (DSD-XY groups)? SUMMARY ANSWER: The GBY candidate genes DDX3Y and TSPY are expressed in the germ cells of DSD-XY patients from distinct etiologies: patients with mixed gonadal dysgenesis (MGD) and sex chromosome mosaics (45, X0/46, XY; 46, XX/46, XY); patients with complete androgen insensitivity (CAIS), patients with complete gonadal dysgenesis (CGD; e.g. Swyer syndrome). WHAT IS KNOWN ALREADY: A GBY locus was proposed to be present on the human Y chromosome because only DSD patients with a Y chromosome in their karyotype have a high—although variable—risk (up to 55%) for germ cell tumour development. GBY was mapped to the proximal part of the short and long Y arm. TSPY located in the proximal part of the short Y arm (Yp11.1) was found to be a strong GBY candidate gene. It is expressed in the germ cells of DSD-XY patients with distinct etiologies but also in foetal and pre-meiotic male spermatogonia. However, the GBY region extends to proximal Yq11 and therefore includes probably more than one candidate gene. STUDY DESIGN, SIZE, DURATION: Protein expression of the putative GBY candidate gene in proximal Yq11, DDX3Y, is compared with that of TSPY in serial gonadal tissue sections of 40 DSD-XY individuals from the three DSD patient groups (MGD, Complete Androgen Insensitivity Syndrome [CAIS], CGD) with and without displaying malignancy. Expression of OCT3/4 in the same tissue samples marks the rate of pluripotent germ cells. PARTICIPANTS/MATERIALS, SETTING, METHOD: A total of 145 DSD individuals were analysed for the Y chromosome to select the DSD-XY subgroup. PCR multiplex assays with Y gene specific marker set score for putative microdeletions in GBY Locus. Immunohistochemical experiments with specific antisera mark expression of the GBY candidate proteins, DDX3Y, TSPY, in serial sections of the gonadal tissue samples; OCT3/4 expression analyses in parallel reveal the pluripotent germ cell fraction. MAIN RESULTS AND THE ROLE OF CHANCE: Similar DDX3Y and TSPY protein expression patterns were found in the germ cells of DSD-XY patients from each subgroup, independent of age. In CAIS patients OCT3/4 expression was often found only in a fraction of these germ cells. This suggest that GBY candidate proteins are also expressed in the non-malignant germ cells of DSD-XY individuals like in male spermatogonia. LIMITATIONS, REASONS FOR CAUTION: Variation of the expression profiles of GBY candidate genes in the germ cells of some DSD-XY individuals suggests distinct transcriptional and translational control mechanisms which are functioning during expression of these Y genes in the DSD-XY germ cells. Their proposed GBY tumour susceptibility function to transform these germ cells to pre-malignant GB/Germ Cell Neoplasia in Situ (GB/GCNIS) cells seems therefore to be limited and depending on their state of pluripotency. WIDER IMPLICATIONS OF THE FINDINGS: These experimental findings are of general importance for each individual identified in the clinic with DSD and a Y chromosome in the karyotype. To judge their risk of germ cell tumour development, OCT3/4 expression analyses on their gonadal tissue section is mandatory to reveal the fraction of germ cells still being pluripotent. Comparative expression analysis of the GBY candidate genes can be helpful to reveal the fraction of germ cells with genetically still activated Y chromosomes contributing to further development of malignancy if at high expression level. STUDY FUNDING/COMPETING INTEREST(S): This research project was supported by a grant (01GM0627) from the BMBF (Bundesministerium für Bildung und Forschung), Germany to P.H.V. and B.B. The authors have no competing interests.